Identification of a Pain-Specific Gene Expression Profile for Pediatric Recurrent Abdominal Pain - Willits, Adam B.; Grossi, Victoria; Glidden, Nicole C.; Hyams, Jeffrey S.; Young, Erin E. (Frontiers in Pain Research, 2021)
Objectives: Functional Abdominal Pain (FAP) and Irritable Bowel Syndrome (IBS) are common recurrent abdominal pain diagnoses with the hallmark, lack of inflammation. To identify a biological signature for IBS/FAP in the colon, this study used genetic profiling to uncover gene expression changes associated with IBS/FAP and abdominal pain. Methods: Patients (8 to 17 years) newly diagnosed with IBS or FAP were enrolled in the study. At diagnostic colonoscopy, 3 rectal biopsies were collected, and gene expression analysis was performed using a Qiagen PCR Array. Relative fold difference in gene expression for 84 pain-associated genes was calculated using the 2-ΔΔ Cq method compared with pain-free controls. Factors affecting pain burden (Pain Burden Interview; PBI) were analyzed, including age, sex, rectal inflammation, and gene expression. Data were analyzed using multiple stepwise linear regression and 2-tailed t tests (P ≤ 0.05). Results: Of the twenty-two total patients in the study, nineteen were diagnosed with either IBS-Constipation (frequency of 5.26%), IBS-Diarrhea (47.37%), IBS-Mixed (10.53%), or FAP (36.84%). IBS/FAP patients reported significantly higher pain burden at the time of diagnosis compared to pain-free controls (p < 0.001), as well as significantly higher abdominal pain (p = 0.01). Of the 84 genes, expression of GRIN1 (p = 0.02), MAPK3 (p = 0.04), P2X4 (p = 0.04), and PTGES3 (p = 0.02) were all significantly associated with PBI score. Discussion: Abdominal pain associated with IBS/FAP in pediatric patients may be linked to the expression of GRIN1, MAPK3, P2X4, and PTGES3, pointing to potential novel therapeutic targets for management of recurring abdominal pain.